Genetic determinants of metamizole metabolism modify the risk of developing anaphylaxis. Issue 9 (September 2015) - García-Martín, Elena; Esguevillas, Gara; Blanca-López, Natalia; García-Menaya, Jesús; Blanca, Miguel; Amo, Gemma; Canto, Gabriela; Martínez, Carmen; Cordobés, Concepción; Agúndez, José A.G.
Abstract : Metamizole is a NSAID that has been banned in several countries because of its toxicity. It is often involved in selective hypersensitivity reactions and most hypersensitivity patients develop anaphylaxis. Metamizole is rapidly metabolized, and metabolic profiles are related to genetic factors. We analyzed whether genetic determinants of metamizole metabolism influence the risk of developing hypersensitivity in 265 patients diagnosed with hypersensitivity to metamizole and 362 healthy individuals who tolerated metamizole. Slow acetylation is associated with an increased risk of developing selective hypersensitivity to metamizole [odds ratio for slow alleles=2.17 (95% confidence interval=1.44–3.27); P =0.00016], and particularly anaphylaxis [odds ratio=4.77 (95% confidence interval=2.28–9.98); P =0.000006], with a significant gene–dose effect. The association was not identified in patients with cross-hypersensitivity. Cytochrome P450 2C9 ( CYP2C9 ) and cytochrome P450 2C19 ( CYP2C19 ) genotypes did not influence risk association. Our findings raise the hypothesis of genetically determined metabolic variability as a risk factor for developing anaphylaxis with metamizole.